Enhanced sensing of liquid levels: multipoint detection using twisted polymer optical fiber in cylindrical configurations - Khadijah Idris@Othman, Siti; Haroon, Hazura; Abdul Razak, Hanim (Bulletin of Electrical Engineering and Informatics, 2025)
Recent interest in water level detection is driven by the need for accurate monitoring in sectors such as agriculture, flood management, and environmental conservation. The measuring of liquid levels and solution concentrations is critical in a variety of industrial sectors. This research is to design, implement, and test the use of plastic optical fiber (POF) as an optical sensor for sensing multi-point liquid levels and densities. The developed device includes a multi-point liquid level sensor that uses refractive index modification of macro bend POFs selectively twisted around a cylindrical column. When the POFs were submerged in various mediums such as pure water, seawater, saltwater, and cooking oil, a set of U-shaped detecting heads was designed to detect changes in liquid levels. The experimental setup included an 850 nm optical light source and a power meter to measure the output power. A comparison of the performance of straight, bent, and twisted POF forms revealed that the twisted and bent POF topologies attained a sensitivity of 30%, exceeding bending-only 21% and twisting-only 12% configurations. In summary, changes in liquid levels resulted in an increase in output power for all liquid media, highlighting the potential of POF as a reliable sensor for sensing liquid levels.